(untitled) (Comprehensive Journal of Science, 2025)
In the recent years, parkinson’s disease has been distributed widely over the world specifically among elderly people. The major aim of this research is find out the availability rates for the essential parkinson’s disease medications (PDMs) as well as studying the suitability of storage conditions of medications in the major cities of Nafusa Mountain, Libya. A survey was completed after a field visit to the major hospitals and to the biggest private pharmacies in the area of study. The results showed that the essential PDMs were not available in the public sector. In the private sector, the highest availability rate were 66.66% in Gharyan pharmacy. The availability rates of biperiden and levodopa/carbidopa were 10% and 20% respectively in the private sector. Regarding the suitability of storage conditions of medicines in the dispensing area, the storage conditions were 100% compliance in AlAwainiya hospital (public sector), Jadu hospital (public sector), Jadu pharmacy (private sector) and Al-Zintan pharmacy (private sector). It is recommended to address the root causes of the low availability of essential PDMs in both sectors. In additions, try to improve the storage conditions for medicines in the dispensing areas.